WEB APPLICATIONS NATIONAL MUSEUM Using Macromedia Dreamweaver MX - Eka Eka (Jurnal Sistem Informasi, 2008)
Museum Web site application programs are created using Macromedia DreamweaverMX program whose goal is to present the National Museum into an Internet network thatcan be opened by anyone who is interested and also want to learn or understand fromabout about this museum. From the home.htm page we can move to the next page with alink without having to go back to the home page.Use Frame, Link and others in making this program a facility has been provided byMacromedia Dreamweaver MX to make it easier for it to make a web page.